158k views
5 votes
What are the solutions to the quadratic equation -2x^2 + 6x + 3 = 0?

User Dayum
by
5.6k points

1 Answer

4 votes

For this, we will be using the quadratic formula, which is
x=(-b+/-√(b^2-4ac))/(2a), with a=x^2 coefficient, b=x coefficient, and c = constant. Our equation will look like this:
x=(-6+/-√(6^2-4*(-2)*3))/(2*(-2))


Firstly, solve the multiplications and the exponents:
x=(-6+/-√(36+24))/(-4)


Next, do the addition:
x=(-6+/-√(60))/(-4)


Next, your equation will be split into two:
x=(-6+√(60))/(-4),(-6-√(60))/(-4) . Solve them separately, and your answer will be
x=-0.436,3.436

User Dave Delay
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.